ADDIE Based Islamic Values Integrated Social Studies Ebook Development: Enhancing Nusantara Islam Conceptual Understanding and Religious Character among Madrasah Students - Muhammad Zainal Abiddin; Turhan Yani; Nuansa Bayu Segara (FKIP - Universitas Riau, 2026)
Social Studies learning in madrasah requires instructional materials that connect social concepts with Islamic values, yet available materials often remain general and less systematic. This study aimed to develop an Islamic values integrated Social Studies ebook on international cooperation and examine its validity, practicality, and effectiveness in improving students' conceptual understanding of Nusantara Islam and religious character. This research employed a Research and Development approach using the ADDIE model combined with a quasiexperimental nonequivalent control group design involving 50 students at MTs Taswirul Afkar Surabaya. Data were collected through needs analysis, expert validation sheets, practicality questionnaires, conceptual understanding tests, and a religious character inventory. The product mapped international cooperation content with Nusantara Islamic values, including ta'awun, ukhuwah insaniyah, and wasathiyyah, and was developed into an ebook containing concept maps, contextual materials, reflection activities, worksheets, and evaluation tasks. Expert validation showed high feasibility in the media dimension (97.4%) and content dimension (98.5%), while student practicality responses were very good. Implementation results indicated that the ebook improved conceptual understanding and supported religious character development. Thus, the ebook is valid, practical, and effective as a value integrated digital instructional material for madrasah Social Studies learning.